2013
DOI: 10.1093/neuonc/not015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of IDH1 mutations in gliomas by immunohistochemistry and DNA sequencing

Abstract: IHC is an easy and quick method of detecting IDH1-R132H mutations, but there may be some discrepancies between IHC and DNA sequencing. Although there were no false-negative cases, cross-reactivity with IDH1-R132L was seen in 3, a finding not reported thus far. Because of more universal availability of IHC over genetic testing, cross-reactivity and staining heterogeneity may have bearing over its use in detecting IDH1-R132H mutation in gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 43 publications
7
83
1
9
Order By: Relevance
“…IDH1 was totally absent in astrocytosis (100%) and was expressed in 60% (18 / 30) The results of the present study were also different from previous study performed by Agarwal et al, 2013 [26] who assessed IDH1 mutation in 88% of diffuse astrocytoma cases. So they suggested that IDH1 occurs as an early event in glioma genesis.…”
Section: Resultscontrasting
confidence: 99%
“…IDH1 was totally absent in astrocytosis (100%) and was expressed in 60% (18 / 30) The results of the present study were also different from previous study performed by Agarwal et al, 2013 [26] who assessed IDH1 mutation in 88% of diffuse astrocytoma cases. So they suggested that IDH1 occurs as an early event in glioma genesis.…”
Section: Resultscontrasting
confidence: 99%
“…The combination of our findings with the literature indicates high TrxR1 expression in primary IDH1 wild type glioblastoma, which is a more aggressive neoplasm, and lower TrxR1 expression with enhanced IDH mutation in secondary glioblastoma, which is a relatively less aggressive neoplasm (1,4,5,17). As indicated previously, this may be an explanation…”
Section: █ Conclusionsupporting
confidence: 86%
“…In addition to R132H/R132C/R132G IDH1, several rarer IDH1 mutations in gliomas have been identified, including R132S/R132L/R132V IDH1 (5,6,41,42). In vitro kinetic assays have shown that R132S and R132L IDH1 catalyze production of D2HG at rates similar to the more common R132H and R132C IDH1 mutations (13,25).…”
Section: Generation Of Idh1 Mutants Engineered To Explore Mechanisticmentioning
confidence: 99%